1996
DOI: 10.1002/ana.410400510
|View full text |Cite
|
Sign up to set email alerts
|

Lambert‐eaton myasthenic syndrome immunoglobulins react with multiple types of calcium channels in small‐cell lung carcinoma

Abstract: Barium currents through voltage-gated calcium (Ca2+) channels were studied in the small-cell lung carcinoma cell line NCI-H345 using patch clamp techniques. Pharmacological dissection of whole-cell barium currents revealed that 23% of the current was sensitive to nitrendipine, 35% to omega-conotoxin GVIA, and between 10 and 39% to omega-Aga-IVA. This implies that these cells express L-, N-, and P-type calcium channels. Only large cells expressed current that was sensitive to omega-Aga-IVA. The size dependency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 54 publications
(32 reference statements)
2
48
0
Order By: Relevance
“…Antibodies to this intracellular subunit would not be expected to cause functional effects on VDCCs in living cells. Previous workers (28)(29)(30) have shown that LEMS IgG blocks both P-type and N-type VDCCs in a human SCLC cell line and N-type and L-type VDCCs in human neuroblastoma cell lines. However, the data presented here suggest that the ␣ 1B subunit is not a general target of antibodies in a clinically representative sample of six LEMS patients.…”
Section: Discussionmentioning
confidence: 91%
“…Antibodies to this intracellular subunit would not be expected to cause functional effects on VDCCs in living cells. Previous workers (28)(29)(30) have shown that LEMS IgG blocks both P-type and N-type VDCCs in a human SCLC cell line and N-type and L-type VDCCs in human neuroblastoma cell lines. However, the data presented here suggest that the ␣ 1B subunit is not a general target of antibodies in a clinically representative sample of six LEMS patients.…”
Section: Discussionmentioning
confidence: 91%
“…Patients with the Lambert-Eaton syndrome present with proximal leg weakness that is caused by antibodies directed against the voltage-gated calcium channels. 25,26 Paraneoplastic encephalomyelitis and sensory neuropathy are caused by the production of an antibody (anti-Hu) that cross-reacts with both small cell carcinoma antigens and human neuronal RNA-binding proteins, resulting in multiple neurologic deficits. 27 SCLC cells also can produce numerous polypeptide hormones, including adrenocorticotropic hormone (ACTH) and vasopressin (ADH), which cause Cushing syndrome and hyponatremia of malignancy, respectively.…”
mentioning
confidence: 99%
“…VGCCs are composed of a number of pharmacologically and electrophysiologically distinct subtypes. Although antibodies have been described that bind to the L-, N-and P-/Q-VGCC subtypes (Meriney et al 1996), only those directed against the P-/Q-subtype, which is responsible for pre-synaptic neurotransmitter release at the neuromuscular junction, have been shown to be pathogenic (Pinto et al 1998).…”
Section: Lambert Eaton Myasthenic Syndromementioning
confidence: 99%